Manifestations of despair in Al-Akli's poetry - Abd Beshr, Abd Mahmoud (Journal of Tikrit University for Humanities, 2024)
This research advances the study to clarify the reality that vagabond poets live or suffer from in the Islamic era, and to identify their methods in confronting that reality, confronting it, and everything that is consistent with their situation, personality, and potential. Accordingly, this research studies an example of a vagabond and lethal poet in the Islamic era: Ibn Uqish Al-Akli, for whom the specter of despair clearly collapsed in his poetry, which represented for him the flowing pulse of life and freedom, which was practiced by the ruling system and the tribe because he felt dissatisfied and accepting of what he encountered in this society in which he lived and about his social situation by imposing a system, principles and customs. It is different from that which people like him believe in, and it is natural for the burning in his soul to rise, and the sighs of deprivation to rise, because he suffered all manifestations of deprivation as he draws pictures of injustice and persecution, and the research relies mainly on poetic texts to reach its goal, using more than one method in the hope of a more accurate explanation. Clearly and comprehensively, noting that the analytical nature is most apparent in reading the poetic text.